Optimal Use Of ANN In The Integration Between Digital Image Processing And Encryption Technique - Fahdel Al-Abaidy, Shaimaa Abbas (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently An ANN is the very much powerful and strong technology for solving various real world-real time issues in area of image processing such as medical, research center etc. This paper represents the Artificial Neural network in combination with the image processing. The main aim of this paper is to study the ANN in integration with digital image processing and encryption technologies. So in this sense we discussed the basics of image processing, digital image processing, artificial neural network and encryption. With the help of proposed block diagram we discussed ANN with and without encryption. When an ANN is used with digital image processing several algorithms are available. Here we discussed the few algorithms in shortly with their iteration equation used at time of learning the ANN.